2014
DOI: 10.1007/s10863-014-9583-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in mitochondrial (dys)function: Implications for neuroprotection

Abstract: Decades of research have revealed numerous differences in brain structure size, connectivity and metabolism between males and females. Sex differences in neurobehavioral and cognitive function after various forms of central nervous system (CNS) injury are observed in clinical practice and animal research studies. Sources of sex differences include early life exposure to gonadal hormones, chromosome compliment and adult hormonal modulation. It is becoming increasingly apparent that mitochondrial metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 166 publications
(203 reference statements)
6
85
0
2
Order By: Relevance
“…Sex differences in behavioral outcome following HI are most likely due to a combination of compensatory mechanisms and sexually dimorphic cell death proclivity (reviewed in Hill and Fitch, 2012; Demarest and McCarthy, 2015). In the current study, we observed a slight, but significant, increase in neuronal cell death in the contralateral hemisphere of the male, but not female, brain following HI (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in behavioral outcome following HI are most likely due to a combination of compensatory mechanisms and sexually dimorphic cell death proclivity (reviewed in Hill and Fitch, 2012; Demarest and McCarthy, 2015). In the current study, we observed a slight, but significant, increase in neuronal cell death in the contralateral hemisphere of the male, but not female, brain following HI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that the male brain is more susceptible to the hypoxia–reperfusion component of HI injury than the female brain. The sexually dimorphic cell death pathways (reviewed in (Hill and Fitch, 2012; Demarest and McCarthy, 2015) likely play a role in the female resilience to hypoxia–reperfusion injury. The female cell death proclivity for caspase-dependent cell death, combined with their higher levels of intrinsic X-linked Inhibitor of apoptosis (XIAP) protein (Hill et al, 2011b), an endogenous caspase inhibitor, may account for the relative resilience of the female brain to hypoxia–reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…An essential step in the development of effective neuroprotective therapies is to better understand cell mechanisms that lead to cell death during ischemia and how sex differences impact on these mechanisms. Fundamental cell signaling pathways such as mitochondrial metabolism and apoptotic cascades (Demarest and McCarthy, 2015) have been shown to be different in males and females and more specifically, it is increasingly recognized that the response to cerebral injury in-vivo and in-vitro is at least partially a function of the sex of the cell. These differences in activation of apoptotic pathways also vary with age.…”
Section: Sexually Dimorphic Cellular Mechanisms Relevant In Ischemic mentioning
confidence: 99%
“…This review summarizes sex differences in selected cellular mechanisms that may contribute to clinical differences between male and female stroke patients. These mechanisms include apoptotic signaling cascades in neurons and glia, resident microglial activation, neuro-glial response to ionic imbalance, autophagy, and mitochondrial toxicity (Ahnstedt et al, 2016;Demarest and McCarthy, 2015). Further progress in understanding and manipulating these mechanisms can lead to the identification of endogenous and therapeutic neuroprotective agents with successful clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS/NOS is well documented in neurodegenerative disorders, such as Parkinson’s, Alzheimer’s, and Huntington’s diseases, and multiple sclerosis (Abou-Sleiman et al, 2006; Beal, 1995, 1998). Also, a recent review article delineates the sex difference in various mitochondrial functions with respect to CNS diseases (Demarest and McCarthy, 2015). …”
Section: Introductionmentioning
confidence: 99%